Building Information Modelling Penetration Factors in Malaysia - W. I. Enegbuma; Y. A. Dodo; K. N. Ali (International Journal of Advances in Applied Sciences, 2014)
The construction industry master plan in Malaysia provides ample leverage towards information technology improvements in the construction industry. Building Information Modelling (BIM) transforms the means to which the traditionally thought method is construction is carried out. Changes occur in aspects of people, process and technology during such transformation. Information technology (IT) acceptance theories of Theory of Reasoned Action (TRA), Technology Acceptance Model (TAM), Theory of Planned Behaviour (TPB), Innovation Diffusion Theory (IDT), Decomposed Theory of Planned Behaviour (DTPB), Extension of Technology Acceptance Model (TAM2) and Unified Theory of Acceptance and Use of Technology stipulates underlining theories to accessing user perception to new systems such as BIM. This paper presents the linking paths to factors of user perceptions (people, process and technology) and how they react in strategic IT implementation and collaborative environment to fully support extensive BIM penetration in the industry. The study further extends the BIM penetration model by Enegbuma and Ali (2012). The model will aid industry practitioners to tackle the various challenges experienced with BIM implementation. Future research will focus on solidifying the proposal with data analysis.